The impact of point‐of‐care hepatitis C testing in needle and syringe exchange programs on linkage to care and treatment uptake among people who inject drugs: An Australian pilot study. Issue 5 (21st March 2022) - Howell, Jessica; Traeger, Michael W.; Williams, Bridget; Layton, Chloe; Doyle, Joseph S.; Latham, Ned; Draper, Bridget; Bramwell, Frances; Membrey, Dean; McPherson, Maggie; Roney, Janine; Stoové, Mark; et al.
Abstract: Point‐of‐care (POC) diagnostics overcome barriers to conventional hepatitis C (HCV) testing in people who inject drugs. This study assessed impact on hepatitis C treatment uptake of POC HCV testing in needle and syringe exchange programs (NSPs). Rapid EC was a single‐arm interventional pilot study of HCV POC testing conducted in three inner‐city community clinics with NSPs. Twelve months after the POC testing, a retrospective medical record and Pharmaceutical Benefits Scheme audit was performed to determine the number of HCV RNA‐positive participants who were prescribed HCV treatment. 70 HCV RNA‐positive Rapid EC study participants were included. 44 (63%) were prescribed DAAs; 26 (59%) completed treatment and 15 (34%) had SVR testing, all of whom were cured. Age ≥ 40 years (aOR 3.45, 95% CI 1.10–11.05, p = .03) and secondary school education (aOR 5.8, 95% CI 1.54–21.80, p = .009) had higher likelihood of being prescribed DAAs, whereas homelessness was inversely associated with prescription of DAAs (aOR 0.30, 95% CI 0.09–1.04, p = .057). Median time to receive a DAA script from date of diagnosis was seven days (IQR 0 to 14 days), and time to filling the DAA prescription was 2 days (IQR 0–12 days). In conclusion, provision of POC testing through NSPs was effective for linking new clients to HCV treatment and reduced the time to treatment. Further studies are needed to define the most cost‐effective use of POC testing in models of care for people who inject drugs to increase HCV treatment uptake.